2014
DOI: 10.1097/wnr.0000000000000204
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between uncinate fasciculus white matter integrity and verbal memory proficiency in children

Abstract: During childhood, verbal learning and memory are important for academic performance. Recent fMRI studies have reported on the functional correlates of verbal memory proficiency, but few have reported the underlying structural correlates. The present study sought to test the relationship between fronto-temporal white matter integrity and verbal memory proficiency in children. Diffusion weighted images were collected from 17 Black children (age 8–11 years) who also completed the California Verbal Learning Test. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 18 publications
1
22
0
Order By: Relevance
“…Correlation between brain imaging findings and verbal working memory has previously been documented in children with different pathological conditions, for example, following traumatic brain injury or in temporal lobe epilepsy . In addition, two previous studies have shown correlations between WM and verbal memory proficiency in healthy children . In older children and adolescents, Mabbott et al.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…Correlation between brain imaging findings and verbal working memory has previously been documented in children with different pathological conditions, for example, following traumatic brain injury or in temporal lobe epilepsy . In addition, two previous studies have shown correlations between WM and verbal memory proficiency in healthy children . In older children and adolescents, Mabbott et al.…”
Section: Discussionmentioning
confidence: 93%
“…The external capsule contains association fibers that connect distant cortical regions. For example, the uncinate fasciculus passes through the external capsule and was previously found to be associated with verbal memory . Inferior fronto‐occipital fasciculus fibers also pass through the external capsule and have been reported to be associated with verbal memory in patients with temporal lobe epilepsy .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations